2018
DOI: 10.1097/mej.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Can an age-adjusted D-dimer level be adopted in managing venous thromboembolism in the emergency department? A retrospective cohort study

Abstract: For patients over the age of 50 years suspected of having VTE with a low pretest probability, increasing the D-dimer cut-off level to 5× the age increases the proportion of patients in whom VTE can safely be excluded without radiological imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Because three participating centers in the PALLADIO study used D-dimer tests with reduced thresholds, we similarly decided to halve the age-adjusted cut-off in patients older than 50 years, but we kept the conventional fixed threshold for patients up to 50 years, as suggested by a previous laboratory study [16]. However, our results confirmed the safety of the approach proposed by Jaconelli and Nobes [20,21].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Because three participating centers in the PALLADIO study used D-dimer tests with reduced thresholds, we similarly decided to halve the age-adjusted cut-off in patients older than 50 years, but we kept the conventional fixed threshold for patients up to 50 years, as suggested by a previous laboratory study [16]. However, our results confirmed the safety of the approach proposed by Jaconelli and Nobes [20,21].…”
Section: Discussionsupporting
confidence: 58%
“…Two recently published studies evaluated lower ageadjusted thresholds. Jaconelli et al evaluated 1649 patients admitted to the emergency department with a suspected DVT or PE, and who had D-dimer testing [20]. Because the HemosIL D-dimer is measured in D-DU and the conventional cut-off is < 230 ng mL À1 , the authors compared the standard cut-off level (230 ng mL À1 in all patients) with a halved age-adjusted threshold (defined as patients age 9 5 ng mL À1 for patients 50 years or older and 250 ng mL À1 for patients younger than 50 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][47][48][49][50][51] One study used the HemosIL D-dimer assay, which reported results in DDU that are equivalent to approximately half of an FEU, and the formula for age adjustment was adjusted accordingly (ageÂ5 mg/L). 52 The primary concern when using an age-adjusted D-dimer cutoff is whether increasing the threshold increases the risk of missed PEs. This measure was expressed as sensitivity in some studies, yet was variably reported as the number of false negatives or "failure rate" in others.…”
Section: Potential Benefits Of Implementing the Recommendationsmentioning
confidence: 99%
“…In light of these results, it appears that when one addresses a geriatric population, the sensitivity of the test is not affected by age, only its specificity is, making it less interesting because of the proportionally growing false positives. Therefore, several scientific studies proposed an age-adjusted DD cut-off [13], and a recent metaanalysis [4] supported that using a strategy of adjusting the DD for age modestly increases the proportion of patients with a negative DD result, which may reduce the need for advanced imaging in approximately 5% to 10% of patients, without a significant increase in missed cases of PE.…”
Section: Discussionmentioning
confidence: 99%